Does climate influence spatial variation of tree species alpha diversity in the Brazilian Atlantic rainforest? - Cerqueira, Roberta Macedo; Martins, Fernando Roberto (Acta Scientiarum. Biological Sciences, 2015)
We tested the hypothesis that the variation in tree species alpha diversity is driven by climate in the Brazilian Atlantic Rainforest (ARF). Considering 139 samples of trees with DBH ≥ 4.8 cm, we correlated alpha diversity measures (Shannon heterogeneity index H’, Chao I richness estimator, and Simpson concentration index C) with climate variables (perhumidity index, mean annual rainfall, and mean annual temperature) and spatial variables (latitude, longitude, and altitude). Using CCA, multiple regression analysis and RDA procedures, we found a positive relationship between latitude, longitude, and altitude with Shannon’s diversity index and Chao I richness estimator, and a negative relationship with Simpson concentration index. Over 75% of the variation remained unexplained and were attributed to stochastic processes. These results indicate that climate has a very weak influence on tree species alpha diversity, which is more influenced by spatial variation in the ARF. We propose that the current tree species alpha diversity could be a result of the history of the ARF during the Cenozoic, when geological events and climate oscillations could have triggered biogeographic processes, such as alternating episodes of vicariance and dispersal, which would have lead to the great diversity of species and heterogeneity across the geographic space observed today.